The Obama Administration and US Relations with the Muslim World (American Journal of Islam and Society, 2009)
On 16 October 2009, the Institute of Global Cultural Studies (IGCS) atBinghamton, jointly with the Association of Muslim Social Scientists ofNorth America (AMSS), sponsored a symposium in Binghamton University’sMandela Hall on “The Obama Administration and US Relations withtheMuslimWorld: Prospects, Progress and Lingering Skepticism.” The presentationsaddressed Iran’s nuclear program, Arab-Israeli relations, Iraq andAfghanistan, Darfur, and studies comparing Obama with Malcolm X andJapan’s new prime minister Yukio Haroyama. Inevitably, there was alsosome debate as to whether Obama’s Nobel Peace Prize was legitimatelyearned or premature ...